The soil nematode community indicates the soil ecological restoration of the Pinus massoniana plantation gap replanted with Cinnamomum longipaniculatum - Chengwei Tu; Qingqing Lu; Ya Zhang; Jiaojiao Tian; Yarong Gao; Yang Liu; Hanbo Yang; Lianghua Chen; Jian Zhang; Jing Wang; Jiujin Xiao (Ecological Indicators, 2022)
Interactions between aboveground and belowground ecosystems components modulate ecosystem functions. However, few studies have focused on the response of soil nematodes to plantation reconstruction. In this study, Cinnamomum longipaniculatum was planted in the gap of a Pinus massoniana plantation. Based on the size, center and edge of C. longipaniculatum patches, the characteristics of the soil nematode community were studied after 8 years of plantation reconstruction. The effect of the C. longipaniculatum plantation on the soil nematode community was related to patch size. The soil nematode community did not change significantly with increasing patch size above 30 m × 30 m. The soil recovered better in the patch center than at the edge, but the edge increased the diversity of soil nematodes with low C-P values. The experimental treatment increased the dominance of soil plant parasite nematodes and bacterivores, decreased the trophic diversity index, and increased the channel ratio, maturity index, enrichment index and structure index of soil nematodes, indicating that soil nutrient cycling improved and the diversity of the soil food web increased. After P. massoniana plantation gaps were replanted with C. longipaniculatum, the main soil properties that affected the soil nematode community were organic carbon, pH, water content and soil aggregate degree. In the soil nematode community, fungal nematodes had the strongest influence on omnivorous-predatory nematodes. Our study showed that the soil environment changed with vegetation and affected soil nematode groups, and soil nematodes effectively reflected soil ecological restoration after P. massoniana plantation gaps were replanted with C. longipaniculatum.